Evaluasi Perbandingan Kinerja Attached Culture Bioreaktor dan Hybrid Membran Bioreaktor dalam Mendegradasi Air Limbah - Juniawan, Asyhar Sururi; Budhijanto, Wiratni; Marbelia, Lisendra (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Restaurant wastewater is categorized as grey wastewater, which is low strength wastewater with a chemical oxygen demand (COD) concentration of <1,000 mg/L. Therefore, further treatment is necessary before it is discharged into the environment. This study focused on comparing the performance of an attached culture bioreactor and a Hybrid Membrane Bioreactor (HMBR) in degrading restaurant wastewater. The bioreactors used a mesh filter support media of 70-80 μm. The bioreactors were operated with COD feed concentration 600 ppm and HRT 13 hour, with artificial grey water waste feed consisting of sugar, urea, KH2PO4, and tapioca flour. The %COD removal achieved by the attached culture bioreactor and HMBR was 90,48% – 90,95% and 96,28%– 96,79%, the turbidity out achieved by the attached culture bioreactor and HMBR was 57,42 – 60,25NTU and 4,95 – 5,62NTU, MLSS value reached  2,36 – 2,86ppm and 2,36 – 2,86ppm. The conclusion of this research shows that the HMBR has relatively better performance than the attached culture bioreactor